Sistema de monitoração e estimativa da produção de energia elétrica de sistemas fotovoltaicos conctados à rede na edificação do GEDAE/PARÁ - SILVA, Yan dos Santos (Universidade Federal do Pará, 2024)
This master's thesis presents the development of mechanisms for monitoring and estimating the electricity production by Grid-Connected Photovoltaic Systems (GCPVS) installed in the building of the Grupo de Estudos e Desenvolvimento de Alternativas Energéticas at the Universidade Federal do Pará (GEDAE/UFPA). The research involves the operational evaluation of the AC side of the GCPVS connected to partial and general electric panels, which are used to aggregate a set of GCPVS and to obtain records from the electrical multi measurement meters via a local monitoring tool. Additionally, the research involves the development of a web-based remote monitoring system for operational monitoring and simulations aimed at estimating the electricity production of the GCPVS. This is achieved by using mathematical models and meteorological data collected through a weather station installed at GEDAE/UFPA, on-site data loggers (as an alternative means of obtaining irradiance and temperature data), and data provided by the National Aeronautics and Space Administration (NASA) platform to fulfill in any gaps caused by system monitoring failures. The results indicate the reliability of the GCPVS measurements in partial panels but also highlight the need to reactivate inoperative systems and implement new systems to improve measurement accuracy in the overall panel. Furthermore, on average, the GCPVS contribute to about 25% of the electricity consumption in the GEDAE/UFPA building, resulting in significant energy cost savings from 2011 to 2023. However, greater savings could be achieved through the restoration of some systems, emphasizing the importance of restoration measures and continuous monitoring of systems performance to increase energy contribution and economic benefits from the use of GCPVS.